Thinking Swarms (Springer Nature, 2025)
This open access book is a multidisciplinary examination of swarm systems including swarm robotics. The book starts with a multidisciplinary consultation performed by the editors with participants from academia, industry and government. The consultation suggested four themes forming parts one to four and grouping the first 16 chapters. Part 1 contains definitions, categorisations and metaphors of swarm systems. Part 2 zooms-in with a behavioural lens on interpretations, narrative theory, and legal frameworks. Part 3 sheds a topological light on cognitive architectures and formations. Part 4 illumes cognitive dimensions on swarm lifelong and curriculum learning and hyper-teaming of swarm systems. The book concludes with future research directions in Part 5. The book is suitable for graduate students and researchers looking for inspiration and novel ideas to explore, or those attempting to understand the diversity of challenges in advanced swarm systems.